Molecular Identification of Rhizobium Isolates and The Effect of Nanoparticles on Growth and Differentiation - al-Hayani, Hanya Khalid; Alhamd , Omar Abdulazeez (Journal for Research in Applied Sciences and Biotechnology, 2023)
In this study, five isolates of Rhizobium bacteria were isolated from several different agricultural regions of Nineveh Governorate. The five isolates showed their ability to dilute gelatin, as well as a positive result of the growth test on a triglyceride medium and iron showed their ability to produce catalase and urease enzyme, and the results of the molecular diagnosis showed The isolates are identical and in varying proportions to the standard isolates recorded in the GenBank, and the biological activity of silver nanoparticles showed a clear antagonistic effect on the growth of rhizobium bacteria, where the first concentration (250) was the least effect, while the third concentration (750) had the highest effect ratio.